Therapeutic Hypothermal In The Treatment Of Hypdxic Ischemic Encephalopath In The Maternal Perinatal National Institute - Medina-Alva, Pilar (2017)
We present the first case of application of therapeutic hypothermia in a newborn with a diagnosis of moderate ischemic hypoxic encephalopathy with the inclusion criterias. Risk factors, diagnostic criteria, evolution and monitoring during hypothermia and the followed-up post-discharge, are reported in our institution.